Effectiveness of Jaw Exercises Applied in Addition to Cervical Stabilization Exercises in Individuals with Chronic Neck Pain: A Randomized Controlled Trial - Canli, Mehmet; Ozudogru, Anil; Alkan, Halil; Cigdem-Karacay, Basak (Dove Medical Press Ltd, 2026)
Purpose: Chronic neck pain (CNP), defined as pain localized to the cervical spine region persisting for more than three months, represents a major global health problem with a steadily increasing prevalence worldwide. This randomized controlled trial aimed to investigate the effectiveness of adding jaw exercises to cervical stabilization exercises on pain, sensorimotor function, and functional outcomes in individuals with CNP. Patients and Methods: A total of 62 individuals aged 18-65 years with cervical spine pain lasting longer than three months and a pain intensity of >= 3 cm on the Visual Analogue Scale (VAS) were included. Participants were randomly allocated to the Rocabado group (RG, n=31) or the control group (CG, n=31). The CG performed cervical stabilization exercises (CSE), while the RG performed Rocabado exercises in addition to CSE for 6 weeks. Pain intensity (VAS), pressure pain threshold and tolerance, balance, cervical range of motion, muscle endurance, Neck Disability Index (NDI), and cervical proprioception were assessed at baseline and posttreatment. Sample size was calculated based on the NDI as the primary outcome. Results: Both groups demonstrated significant improvements in pain intensity, cervical range of motion, muscle endurance, disability, balance, and proprioception after 6 weeks (p<0.05). Compared with the control group, the Rocabado group showed significantly greater improvements in pressure pain threshold and tolerance (eta(2) = 0.29-0.41), cervical propriosepsiyon (eta(2) = 0.14-0.19), and static and dynamic balance parameters (eta(2) = 0.27-0.46), indicating moderate to large group-by-time effects (p<0.05). Conclusion: Adding Rocabado exercises to cervical stabilization exercises provides superior improvements in sensorimotor function and pain-related outcomes in individuals with chronic neck pain. These findings suggest that integrating jaw-focused exercises into cervical rehabilitation programs may offer clinically meaningful benefits. Trial Registration: This clinical trial was registered at http://clinicaltrials.gov (Number: NCT05887349, registration date: 05/23/2023).
Keywords: Pain; Neck Pain; Jaw; Exercise